Experimental Tasks in Chemistry to Strengthen Motivation in Civil Engineering Students (Docentes 2.0 Journal, 2025)
The first two decades of the millennium have been characterized by technological advancements in medicine and engineering. Following the COVID-19 pandemic, Peruvian higher education institutions implemented emergency plans to continue providing educational services. The objective of this research was to determine the effect of contextualized experimental tasks on students' motivation to study chemistry. The study was framed within the positivist paradigm, using the inductive method, a quantitative approach, and a quasi-experimental, explanatory-applied, cross-sectional design. The sample comprised 60 students, divided into a control and an experimental group. The independent variable was the application of contextualized experimental tasks in chemistry, and the dependent variable was students' motivation to study science. The results demonstrated the intervention program's positive effect. The pre-test scores for the control and experimental groups were 45.06% and 44.96%, respectively. After the intervention program was applied, the experimental group showed a score of 84.49%, while the control group showed no significant difference. The hypothesis test demonstrated that the Wilcoxon scale value, the Z-Wilcoxon test statistic, was -6.121, and the significance level was p < 0.005, thus accepting the alternative hypothesis and concluding that the contextualized experimental tasks improved students' motivation to study science.
Keywords: Contextualized experimental task; corrosion; aqueous systems; student motivation; Civil Engineering